(untitled) (Pesquisa Odontológica Brasileira, 2001)
The aim of this study was to verify the relationship between the radiographically measured width of the pericoronal space (PS) and the microscopic features of the follicle in order to contribute to the diagnosis of small dentigerous cysts and paradental cysts. One hundred and thirty unerupted teeth (UT) and thirty-five partially erupted teeth (PET) were radiographed and extracted. The radiographic analysis consisted of measuring the width of the PS. The results of the radiographic analysis were compared with those of the histopathologic examination of the dental follicle. The width of the PS ranged from 0.1 to 5.6 mm. The most frequently observed lining of the follicles was a reduced enamel epithelium (REE) (68.4%) in UT and a hyperplastic stratified squamous epithelium (HSSE) (68.5%) in PET. Inflammation was present in 36.1% of the UT and in 82.8% of the PET. There was a statistically significant association between the presence of stratified squamous epithelium (SSE) and PS enlargement for UT (p < 0.05). There was a tendency of association between inflammation and PS enlargements in PET and, possibly, in UT, despite the absence of statistical significance. Surgically, we did not detect bone cavitation or luminal cystic contents in pericoronal spaces smaller than 5.6 mm. We suggest that the first radiographic diagnosis for a PS enlargement, in most of the routine clinical cases, should be of "inflammation of the follicle". The hypothesis of "dentigerous cyst" or "paradental cyst" is suggested as a second diagnosis. The final differential diagnosis between a small dentigerous or a paradental cyst and a pericoronal follicle depends on clinical and/or surgical findings, such as the presence of bone cavitation and cystic content.